Sosialisasi Penyusunan Manual Halal Bagi UMKM Di Kabupaten Gowa - Parenreng, Syarifuddin Mabe; Handayani, Dwi; Setiawan, Irwan; -, Saiful; Darmawan, Armin; Syamsul, Diniary Ikasari; -, Nilda (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
Mas Dimas Stall and The Dill Restaurant are Micro, Small and Medium Enterprises (MSMEs) that have a restaurant business with various types of food and are famous among students. Both MSMEs want to have a halal logo on their restaurants and also to follow government regulations regarding halal certification, but are constrained by the lack of information circulating in the community so that they have not submitted halal certification to the Halal Guarantee Institution (LPH). Therefore, this community service activity aims to provide and increase knowledge and understanding of MSME actors who will provide information about what steps must be taken by MSME actors to get a halal logo on their business, especially about the documents they must prepare for the preparation of a halal manual which is the initial step for submitting halal certification. The implementation process will begin with the provision of a pre-test then continued with the socialization of the preparation of the halal manual, continued with a discussion and ended with the provision of a post-test. The results of this analysis state that participants' knowledge of the halal manual increased significantly, as can be seen from the results of the pre-test and post-test for the halal theory assessment aspect from 42% to 94%, the systematic preparation of the halal manual from 30% increased to 90% and the report on the preparation of a simple halal manual from 24% to 76%, so it can be stated that this community service activity was successful.